2016
DOI: 10.1111/ggi.12839
|View full text |Cite
|
Sign up to set email alerts
|

Association between gait abnormality and malnutrition in a community‐dwelling elderly population

Abstract: In community-dwelling older adults, malnutrition is related to decreased walking smoothness in the ML direction, suggesting that nutritional status affects lateral trunk control during walking. Geriatr Gerontol Int 2017; 17: 1155-1160.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…Malnutrition and weight loss, body mass index (BMI) values lower than 20 kg/m 2 , reduced food intake in general and reduced protein intake specifically are established independent factors which negatively influence functional parameters in older people [3,4]. While nutritional status and its association with functionality has been well examined in community-dwelling older individuals [5][6][7], in older hospital patients [2,8] and in nursing home residents [9,10], only scarce information is available in geriatric rehabilitation. The majority of patients in a geriatric rehabilitation setting is significantly older than 70 years, multimorbid and has a reduced functional status, which necessitates nursing care for activities of daily living [11].…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition and weight loss, body mass index (BMI) values lower than 20 kg/m 2 , reduced food intake in general and reduced protein intake specifically are established independent factors which negatively influence functional parameters in older people [3,4]. While nutritional status and its association with functionality has been well examined in community-dwelling older individuals [5][6][7], in older hospital patients [2,8] and in nursing home residents [9,10], only scarce information is available in geriatric rehabilitation. The majority of patients in a geriatric rehabilitation setting is significantly older than 70 years, multimorbid and has a reduced functional status, which necessitates nursing care for activities of daily living [11].…”
Section: Introductionmentioning
confidence: 99%
“…GS, as a relevant functional status indicator, is another objective measure that is expected to be associated with nutrition status. It was advanced that in older adults undernutrition could affect lateral trunk control during walking . A low GS has also been proposed both as a marker of undernutrition, identified using MNA‐SF, and overweight and obesity, which were assessed through BMI …”
Section: Introductionmentioning
confidence: 99%
“…It was advanced that in older adults undernutrition could affect lateral trunk control during walking. 14 A low GS has also been proposed both as a marker of undernutrition, identified using MNA-SF, 15,16 and overweight and obesity, which were assessed through BMI. 16,17 Nutrition status assessments are not always carried out considering both objective nutrition and functional indicators.…”
Section: Introductionmentioning
confidence: 99%
“…The proprioceptive sensation of the periodontal ligament plays an important role in controlling body balance when walking . As an indirect mechanism, malnutrition may lead to declines in walking . Our cross‐sectional study reported that insufficient protein intake is associated with walking speed .…”
Section: Discussionmentioning
confidence: 64%
“…24 As an indirect mechanism, malnutrition may lead to declines in walking. 25 Our cross-sectional study reported that insufficient protein intake is associated with walking speed. 13 Previous studies reported that older Japanese adults with fewer occlusal supports on their natural teeth or lower occlusal force had significantly lower intake levels of multiple nutrients, including protein, and vitamins A, D and E. 26,27 Shortages of these nutrients may play important roles in declines in muscle mass, muscle strength and physical performance.…”
Section: Previous Research Suggests Several Plausible Mechanisms To Ex-mentioning
confidence: 77%